Geriatric Goalposts: Of Independence And Interdependence - Minakshi Dhar; Monika Pathania; Deepak Khandelwal; Sanjay Kalra (Journal of the Pakistan Medical Association, 2023)
Our elder population has a unique set of needs and necessities, challenges and concerns. This reflects in the approach of geriatric medicine, which aims to ensure functional freedom and independence, as well as healthy ageing, of older citizens. We propose another, higher, aim of geriatric medicine: that is interdependence. This creates a spirit of optimism, in persons of geriatric age group as well as in their health care providers, who are able to interpret goals of medical care in a broader perspective. Keywords: ADL, geriatrics, gerontology, independence, interdependence, Person centred care.